65.5k views
3 votes
2
2. Evaluate (a + y)+ 2y if a = 5 and y = -3.
F 58
G -2
H 70
J 10

1 Answer

0 votes

Answer: G) -2

=======================================================

Step-by-step explanation:

I'm assuming you meant to say (a+y)^2 + 2y

Replace each copy of 'a' with 5. Replace each copy of 'y' with -3. Use PEMDAS to simplify.

(a+y)^2 + 2y

(5 + (-3))^2 + 2(-3)

(5-3)^2 + 2(-3)

(2)^2 + 2(-3)

4 + 2(-3)

4 - 6

-2

So (a+y)^2 + 2y = -2 when a = 5 and y = -3.

User Adam Heeg
by
7.2k points